2019
DOI: 10.5114/biolsport.2019.83958
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of technical activity in various playing positions, in relation to match outcomes in professional soccer

Abstract: The study presented below aimed to examine the position-specific evolution of technical activity among soccer players and how it is related to match outcomes over three consecutive domestic seasons in Germany’s Bundesliga. The research was based on a sample of 13,032 individual match observations of 556 soccer players during the 2014/2015, 2015/2016 and 2016/2017 seasons. These players were classified into five positional roles: central defenders (CD), full-backs (FB), central midfielders (CM), wide midfielder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 41 publications
4
26
0
4
Order By: Relevance
“…Another concern is that the number of crosses continuously decreased and the number of long balls slightly changed among the period of nine seasons, while the percentage of the aerial wins observed a significant increase, especially from the season 2012/2013. This result is in line with the study of Konefał et al (2019) on the German Bundesliga. As the aerial duels usually occurred from crosses and long balls (Liu et al, 2016a), our findings may indicate that the decrease of the crosses has a negative impact on the appearance of the aerial duels.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Another concern is that the number of crosses continuously decreased and the number of long balls slightly changed among the period of nine seasons, while the percentage of the aerial wins observed a significant increase, especially from the season 2012/2013. This result is in line with the study of Konefał et al (2019) on the German Bundesliga. As the aerial duels usually occurred from crosses and long balls (Liu et al, 2016a), our findings may indicate that the decrease of the crosses has a negative impact on the appearance of the aerial duels.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in line with a study on the English Premier League from Barnes et al (2014) in which the evolutionary trends of players' technical performance were identified based on a period of seven consecutive seasons. Nevertheless, opposite changes were observed in Germany's Bundesliga, the number of total shots decreased among playing positions during season 2014/2015 to 2016/2017 (Konefał et al, 2019). This disparity may be due to the relatively smaller database used (three seasons); the identified longitudinal performance characteristics cannot be compared with the seven-season and nine-season period studies.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, a bad shot rate has a great negative impact on the match outcome. The results corroborate the previous finding that shots on target essentially affects the probability of winning in CSL [36] , which implied that shots accuracy and quality are key performance features in CSL games as in other top leagues [26,37] . Moreover, it is shown that shots on target and passes has strong weights in positive and negative features respectively.…”
Section: Feature Importancesupporting
confidence: 90%
“…Probably with the intention of avoiding a comeback or once ahead on the scoreboard. The ball possession indicator is important depending on the league, although it is associated with success in the Bundesliga [32], Spanish League [6] and Premier League [33], or in international tournaments such as the World Cup [34]. Furthermore, it seems that football is evolving towards the possession game, due to an increase in the number and efficiency in passing [35], mainly in players on their defensive line [36].…”
Section: Discussionmentioning
confidence: 99%